Understanding barriers to optimal supervision and delivery of the National Certificate (vocational) curriculum through TVET college lecturers’ reflective evaluations - Angelona Rewhydah Williams; Karel Prins; Bongani Innocent Nkambule; Sindile Amina Ngubane (REID (Research and Evaluation in Education))
Propounded by reflective theory, this qualitative case study drew on TVET lecturers' reflective evaluations of factors that they considered to have a bearing on optimal supervision and delivery of the National Certificate (Vocational) curriculum. Data were collected from participants across three campuses of a TVET college in the Eastern Cape Province, South Africa. Twelve lecturers of different seniority were purposively sampled and interviewed in two focus group sessions. The first focus session involved six participants: four post-level 2 and two post-level 3 personnel recognized by the South African Council for Educators (SACE) as "office -based lecturers" and classified within the middle management echelon of curriculum management and supervision. The second focus group session entailed six post-level 1 personnel (recognized by SACE as "classroom-based lecturers"). The findings problematized (1) the Department of Higher Education and Training’s failure to monitor and evaluate curriculum delivery processes; (2) a lack of comprehensive professional development opportunities for classroom-based lecturers; (3) poor coordination of work-integrated learning (WIL) programs and processes; (4) curriculum supervisors’ limited time for classroom visits due to heavy administrative workload; (5) the absence of communities of practice for knowledge sharing purposes among lecturers; (6) students' language barriers, which led to low pass rates; (7) shortage of qualified student support practitioners and onsite academic support programs; and (8) unreliable Internet connectivity and rigid access to technology infrastructure. The study recommends that the college leadership should address these challenges by applying all possible measures to optimize lecturers' curriculum supervision and delivery practices at the selected TVET college .